INVESTIGATING PRESCHOOL TEACHERS’ TEACHING MATHEMATICS APPROACH AND VIEWS ON THEIR TEACHING SKILLS IN NORTH CYPRUS - Sarem ÖZDEMİR (Fırat University, 2019)
This study aims to explore the self-opinion of teachers’ mathematics teaching skills and approach of teaching mathematics of preschool teachers’ in North Cyprus. In this study, qualitative research design is used and 54 of 252 preschool teachers participated to the study. A questionnaire was used to identify their opinion and approach of teaching mathematics in preschool under three themes that are teaching mathematics skills, use of curriculum and pedagogical content knowledge. According to the findings it was revealed that only 5 of the participants were graduated from preschool teaching department. Rest of the participant did never take courses related with mathematics education. Five pre-school teachers indicated that mathematics education courses were not related with theoretical or practical knowledge but developing educational materials. However all of the participants specified that they have self confidence when teaching mathematics in the class. Some of the teachers pointed out that they struggle when dealing with students who need special education. It is also found that preschool teachers prefer pen-paper activities instead of outdoor playing activities. Results of the study were discussed in line with the related literature.